Dilemas e dificuldades dos professores de matemática do ensino fundamental II em início de carreira - Souza, Ariovaldo Jacquier de (2009)
This research aims at discussing the setbacks and difficulties of Math teachers from Secondary School II at their initial careers. This paper also analyzed the subjects taken during all the teaching process to face these difficulties taking into account the problems the teachers face at beginning of their careers, this paper pried to answer the following questions: (i) Which are the main problems and difficulties highlighted by teachers from Secondary School II at the beginning of their careers on a daily basis? (ii) How do teachers face these difficulties? (iii) What role does the knowledge taken during the learning process play to face these setbacks? This study was supported by Huberman s analyses about the life cycle of the teachers and, more detailed, about the first steps in the teaching process of the teachers. It was adapted a qualitative approach including descriptive and interpretative methods. The data gathering was performed by the means of intensive interviews with six Math teachers from Secondary School II from the scratch of their careers, taking into account the following parameters: profession expectation, ideal/ real impact; support and school scenario, teaching relationship; teacher-student relationship; school material and autonomy. From this point of view it was possible to detect some difficulties that the beginning teacher faces like of support from the owners, coworkers and family, as well as indiscipline and luck of drive from students. The role of the subjects seemed to have little impact in facing the difficulties and setbacks at the beginning of the career of these teachers